Studying Effect of Solar Concentrator Type on Small Signal Gain for Pumping Nd: YAG Crystal - Azzawi, Mohanad M. (University of Thi-Qar Journal of Science, 2019)
In this research, solar flux is applied as a source for pumping Nd:YAG crystal. Lasing action could be gained when there is enough pumped solar flux expressed in term of small signal gain, SSG. Concentration ratio is the term of determining how the solar flux is close to produce SSG for lasing action. Concentration is achieved by applying a concentrator. Two types of concentrators are applied for comparison: Frensel lens and parabolic reflecting dish. It is found that, a solar intensity of 800 W/ m2 incident on Frensel lens of aperture area (729) Cm2 has a concentration ratio of (18000) compared with a parabolic reflecting dish of aperture area (7065) Cm2 has a concentration ratio of (1000). It is clear that Frensel lens is preferred over parabolic reflecting dish because it meets the required value of SSG for lasing Nd:YAG crystal.